Prevalence and correlations with depression, anxiety, and other features in outpatients with chronic obstructive pulmonary disease in China: a cross-sectional case control study - Lou, Peian; Zhu, Yanan; Chen, Peipei; Zhang, Pan; Yu, Jiaxi; Zhang, Ning; Chen, Na; Zhang, Lei; Wu, Hongmin; Zhao, Jing (BMC pulmonary medicine, 2012)
Patients with chronic obstructive pulmonary disease (COPD) often experience depression and anxiety, but little information is available regarding Chinese patients with these conditions. The present study assessed depression and anxiety in Chinese patients with COPD. A case-controlled study was designed with 1100 patients with COPD enrolled in the case group and1100 residents without COPD and respiratory symptoms selected as the control group. Anxiety and depression in both groups were evaluated using the Hospital Anxiety and Depression Scale (HADS). The body mass index,degree of airflow obstruction, dyspnea, and exercise capacity (BODE ) index was used to assess COPD severity. Binary logistic regression models were used to test the association between anxiety and depression. The patients with COPD were more likely than controls to experience depression (cases, HADS 10.5 ± 3.6, prevalence 35.7%; controls, HADS 8.7 ± 2.7, prevalence 7.2%) and anxiety (cases, HADS 10.4 ± 3.1, prevalence 18.3%; controls, HADS 8.6 ± 2.1, prevalence 5.3%). Subjects with anxious and depressive symptoms had poorer health outcomes including a higher BODE index, a shorter 6-minute-walk distance (6MWD), more dyspnea, and a higher St George's respiratory questionnaire (SGRQ) score. The prevalence of anxious and depressive symptoms increased with increasing BODE scores. On the basis of binary logistic regression, the BODE index was significantly correlated with anxiety (OR = 1.47, p < 0.001) and depression (OR = 1.51, p < 0.001). Anxious and depressive symptoms were also associated with several factors including younger age, female sex, higher education level, lower household income and history of smoking. This study confirmed the high prevalence of anxiety and depression in Chinese outpatients with COPD. Patients with COPD who had anxiety and/or depression had a poorer health-related quality of life. Chinese Clinical Trials Registration(ChiCTR-TRC-12001958).